THU0526 Short and long-term follow-up of tocilizumab for severe juvenile idiopathic arthritis-associated uveitis. (15th June 2017) - Vegas-Revenga, N; Calvo-Río, V; Santos-Gόmez, M; Calvo, I; González-Fernández, M; Lόpez-Montesinos, B; Mesquida, M; Adan, A; Hernández, M; Maíz, O; Atanes, A; Bravo, B; et al.
Abstract : Objectives: To assess the efficacy of tocilizumab (TCZ) at short and long term follow-up for severe juvenile idiopathic arthritis-associated uveitis. Methods: Multicentre study of 25 patients who had inadequate response to traditional treatment with corticosteroids and at least one conventional immunosuppressive drug including biological therapy. The outcome variables were the degree of inflammation, visual acuity and macular thickness. The results are expressed as mean±SD for normally distributed variables, or median [IQR] when are not. Comparison of continuous variables was performed using the Wilcoxon test. Results: We studied 25 patients (21 women/4 men); mean age 18.6±8.3. Uveitis was bilateral in 22. JIA subsets were oligoarthritis (n=17), polyarthritis (5), psoriatic (2) and enthesitis-related arthritis (1). Ocular sequelae at TCZ onset were cataracts (13), glaucoma (7), synechiae (10), band keratopathy (12), maculopathy (9), and amblyopia (5). Pattern of uveitis was: anterior (17), panuveitis (4), intermediate (2) and posterior (2). Before TCZ, they had received corticosteroids, conventional immunosuppressive drugs and biologics, including adalimumab (24), etanercept (8), infliximab (7), abatacept (6), rituximab (2), anakinra (1), and golimumab (1). TCZ dosage regimen was 8 mg/kg IV/4 weeks (21), every 2 weeks (2), every 8 weeks (1), or 2.9 mg/kg sc every week (1). All outcome variables showed a rapid and maintained improvement (Table 1 ) after a follow up of one year (n=21), 2 years (n=11), and 3 years (n=5). A reduction in the daily median dose of prednisone from 10 mg [0–15 mg] to 0 [0–0 mg] in 3 years, (p<0.05) was observed. After a median follow-up of 20.5±11.7 months in 4 patients, the interval between TCZ doses was increased to 5 weeks (n=2), 6 weeks (1) and 7 weeks (1) because of remission. TCZ had to be withdrawn due to articular inefficiency (1) or articular and ocular inefficiency (1). The main adverse effects were severe autoimmune thrombocytopenia, autoimmune anemia and thrombocytopenia, pneumonia, viral conjunctivitis and bullous impetigo in 1 patient each. Conclusions: TCZ is useful at short and long term follow-up for severe Juvenile Idiopathic Arthritis-associated uveitis. It is possible to optimize the TCZ dose. Disclosure of Interest: None declared